The professional life of outstanding figures of medical sciences as incentive in the medicine students training - Yaité Zaldívar Rosales; Homero Calixto Fuentes González; María Eugenia García Céspedes (Centro Provincial de Información de Ciencias Médicas, 2020)
The education and values are human dimensions reciprocally linked. Education constitutes a good value in the way that facilitates the person's development, as for values are included in education, since the society has kept the ends of this, which motivate and guide the inexhaustible search of perfection. In correspondence with the above-mentioned, and on the base of the theoretical matter, the aim of this work was  to contribute in the ethical-professional improvement and of values, in general, during the initial, continuous and permanent training of medicine students, starting from an educational approach and the recognition of the emerged values of outstanding figures in medical sciences that can serve as incentive in this training, in order to achieve a better humanist performance in the professional practice of the new physicians.